Structural irregularities and peculiarities of low-temperature thermal properties of Sn24P19.4Br8 clathrate. Issue 28 (30th June 2017) - Novikov, V. V.; Matovnikov, A. V.; Mitroshenkov, N. V.; Kornev, B. I.; Pilipenko, K. S.; Likhanov, M. S.; Shevelkov, A. V.
Abstract : Temperature changes of the heat capacity and unit cell parameters of Sn24 P19 Br8 clathrate were experimentally determined in the temperature range of 2 to 300 K. Abstract : Temperature changes of the heat capacity and unit cell parameters of Sn24 P19.4 Br8 clathrate were experimentally determined in the temperature range of 2 to 300 K. The data obtained were analyzed using Debye–Einstein approximation and taking into account the impact of both disorder in the host matrix and the presence of vacancies in the framework. Anomalous negative contribution to the thermal expansion was revealed and related to the defect mode influence on the clathrate thermal properties as a result of vibrations of two-level systems (TLS). The guest atoms that have the opportunity to occupy spatially close yet energetically non-equivalent positions in the asymmetric environment of the host matrix atoms play a principal role in the TLS formation. The results are compared with those previously obtained for semiclathrate Ge31 P15 Se8 .